OPTIMALISASI NILAI MANAJEMEN DAN INOVASI BISNIS DALAM RANGKA MENDORONG KEMANDIRIAN USAHA SEKTOR INDUSTRI KREATIF DI JAWA TIMUR - Wahyudiono, Wahyudiono; Estiasih, Soffia Pudji; Aminatuzzuhro; Prawira, Yuda (Jurnal Ilmu Manajemen, 2023)
The purpose of this research is to examine the effect of management values ??on business innovation and business independence and to examine the effect of business innovation on business independence. This research is included in the category of quantitative research with an associative approach accompanied by hypothesis testing. The unit of analysis in this study was creative industry players with a total population of 276. The sample size in this study was 119, while the sample members were taken from the population using a purposive sampling technique, in which the sample members were also referred to as respondents.Path analysis results show that management value directly and significantly influences business innovation and business independence, business innovation directly and significantly influences business independence in the creative industry sector. The findings in this study indicate that optimizing management values ??that are carried out massively and in a structured manner will encourage innovative behavior in managing a business, as well as business innovations that are carried out with full creativity and sustainability will encourage business independence in the creative industry sector to become more effective, both in managing access to resources resources, implementing management policies, business processes and business cycles, thereby spurring the creative industry sector to grow and develop in order to achieve better performance